Criteria for selecting experts in the evaluation of educational technologies in Nursing: an integrative review - Emanuella Silva Joventino Melo; Maria Jocelane Nascimento da Silva; Aline Pereira do Nascimento Silva; Hévila Ferreira Gomes Medeiros Braga; Brena Shellem Bessa de Oliveira; Flávia Paula Magalhães Monteiro; Lorena Pinheiro Barbosa (Universidade Federal do Ceará, 2024)
Objective: to analyze the criteria for selecting experts in studies evaluating the validity of educational technologies in nursing. Methods: an integrative review was carried out in five databases. Full publications from the last five years in Portuguese, English, and Spanish were included. The analysis was carried out by two independent researchers, with the help of a third reviewer. Results: 29 studies were included. The majority chose to adopt criteria drawn up by the authors themselves (n = 18; 62.1%); followed by using other methodological references (n = 7; 24.1%); and the original Fehring or with adaptations (n=4; 13.8%). The criteria analyzed referred to the domains of academic training, professional performance/experience, and productions. Conclusion: most of the studies did not cite a reference to determine the criteria for selecting experts, nor did they establish a minimum score for selecting experts. Contributions to practice: the need for standardization in the selection of experts and the development of new, comprehensive, and up-to-date criteria such as the one proposed is essential to guide researchers and health professionals in the selection of experts for the evaluation of educational technologies in the field of nursing.